Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12889-022-13435-y
|View full text |Cite
|
Sign up to set email alerts
|

Small + Safe + Well: lessons learned from a Total Worker Health® randomized intervention to promote organizational change in small business

Abstract: Background Leadership commitment to worker safety and health is one of the most important factors when organizations develop and implement a Total Worker Health® approach. We aimed to assess the effectiveness of a Total Worker Health (“TWH”) leadership development program that targeted owners and other senior-level leadership positions on changing organizational and worker outcomes from baseline to one-year later. Methods The Small + Safe + Well st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…We found that not only was there a clear need for occupational safety and health technical assistance during the COVID-19 pandemic, but the use of the TWH approach to provide technical assistance was also in demand, acceptable, and practical for participating businesses. Therefore, our study suggests that the TWH approach is feasible in small and medium businesses and that further research on TWH program implementation in this business category is warranted, especially considering reported challenges that small and medium businesses face 10–12 …”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…We found that not only was there a clear need for occupational safety and health technical assistance during the COVID-19 pandemic, but the use of the TWH approach to provide technical assistance was also in demand, acceptable, and practical for participating businesses. Therefore, our study suggests that the TWH approach is feasible in small and medium businesses and that further research on TWH program implementation in this business category is warranted, especially considering reported challenges that small and medium businesses face 10–12 …”
Section: Discussionmentioning
confidence: 90%
“…Therefore, our study suggests that the TWH approach is feasible in small and medium businesses and that further research on TWH program implementation in this business category is warranted, especially considering reported challenges that small and medium businesses face. [10][11][12] We consistently heard feedback supporting the demand, practicality, and acceptability of the PROSPER team's technical assistance services and TWH protocol. Based on their experience with PROS-PER and knowledge of TWH, most participants reported that they would recommend a TWH approach to other small and medium organizations, because it is both a comprehensive approach to worker safety, health, and well-being supporting the whole worker, and appropriate for meeting employee expectations.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Some core characteristics are listed below; for an aggregated overview on a quantitative level, see Table 2. If specified in the studies, the size of the SMEs ranged from less than 20 employees [39] to less than 500 employees [40]. Also, the occupational sectors were found to be heterogeneous across and within the studies, varying from a sake brewery [41] to the social assistance sector [40] to small craft businesses (e.g., hairdresser or painter [42]), as well as mixed samples in Saraf et al [43] (service sector, manufacturing and retailing), Martin et al [44]( transport, finance and retail) and Schwatka et al [45].…”
Section: Study Characteristicsmentioning
confidence: 99%